Managements Theory Regarding the Human Role - Salome Kekelidze (Zien Journals, 2022)
Social and labor relations are a system of interdependence and interaction between the subjects of these relations, which is aimed at regulating the quality of working life and ensuring a high standard of living. The modern stage of the scientific-technical revolution has fundamentally changed the role of man in production. Today's workers must possess strategic thinking skills. Have a broad erudition and high culture. According to this, there's a need for unwavering personnel development. This means taking certain measures to reveal the personal potential of the employees.
Keywords: personal; scientific; strategic; development